Sudden cardiac arrest in sports – need for uniform registration: A Position Paper from the Sport Cardiology Section of the European Association for Cardiovascular Prevention and Rehabilitation. (29th August 2020) - Solberg, EE; Borjesson, M; Sharma, S; Papadakis, M; Wilhelm, M; Drezner, JA; Harmon, KG; Alonso, JM; Heidbuchel, H; Dugmore, D; Panhuyzen-Goedkoop, NM; Mellwig, K-P; et al.
Abstract: There are large variations in the incidence, registration methods and reported causes of sudden cardiac arrest/sudden cardiac death (SCA/SCD) in competitive and recreational athletes. A crucial question is to which degree these variations are genuine or partly due to methodological incongruities. This paper discusses the uncertainties about available data and provides comprehensive suggestions for standard definitions and a guide for uniform registration parameters of SCA/SCD. The parameters include a definition of what constitutes an 'athlete', incidence calculations, enrolment of cases, the importance of gender, ethnicity and age of the athlete, as well as the type and level of sporting activity. A precise instruction for autopsy practice in the case of a SCD of athletes is given, including the role of molecular samples and evaluation of possible doping. Rational decisions about cardiac preparticipation screening and cardiac safety at sport facilities requires increased data quality concerning incidence, aetiology and management of SCA/SCD in sports. Uniform standard registration of SCA/SCD in athletes and leisure sportsmen would be a first step towards this goal.